Innovations in Image-Guided Procedures: Unraveling Robot-Assisted Non-Hepatic Percutaneous Ablation - Chlorogiannis, David-Dimitris; Charalampopoulos, Georgios; Bale, Reto; Odisio, Bruno; Wood, Bradford J.; Filippiadis, Dimitrios K. (Seminars in Interventional Radiology, 2024)
Interventional oncology is routinely tasked with the feat of tumor characterization or destruction, via image-guided biopsy and tumor ablation, which may pose difficulties due to challenging-to-reach structures, target complexity, and proximity to critical structures. Such procedures carry a risk-to-benefit ratio along with measurable radiation exposure. To streamline the complexity and inherent variability of these interventions, various systems, including table-, floor-, gantry-, and patient-mounted (semi-) automatic robotic aiming devices, have been developed to decrease human error and interoperator and intraoperator outcome variability. Their implementation in clinical practice holds promise for enhancing lesion targeting, increasing accuracy and technical success rates, reducing procedure duration and radiation exposure, enhancing standardization of the field, and ultimately improving patient outcomes. This narrative review collates evidence regarding robotic tools and their implementation in interventional oncology, focusing on clinical efficacy and safety for nonhepatic malignancies.
Keywords: interventional oncology; stereotaxy; robotic navigation; ablation; biopsy; interventional radiology